Spatiotemporal mapping of groundwater salinity in Al-Batinah, Oman - Ammar Abulibdeh (15785928) (2021)
The aim of this study is to analyze the spatiotemporal variation of groundwater salinity in Al-Batinah governorate, a Sultanate of Oman, and the strategies to manage and control this problem in an effective way. Around 58,000 water wells were investigated based on their operational status and type between 1990 and 2018. The groundwater salinity levels in the area were classified into five categories based on the electrical conductivity (EC). These categories include fresh water or excellent irrigation water, low salinity water, moderate salinity water, high salinity water, and very high salinity water. A salinity map was created to track the changes in groundwater salinity over time in the study area. The results show that water salinity increases over time due to the increase in urbanization and over-pumping of water from these wells. The increase in water salinity has a negative impact on the sustainability of the society and the economy, particularly on the agricultural sector and hence effective government measurements are required to reduce these negative effects. Other Information Published in: Groundwater for Sustainable Development License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.gsd.2021.100551